A two-chain aspartic protease present in seeds with high affinity for peanut oil bodies. (15th February 2018) - Chen, Yeming; Chen, Yajing; Zhao, Luping; Kong, Xiangzhen; Yang, Zhaoqi; Hua, Yufei
Highlights: One two-chain aspartic protease is identified in peanut crude oil bodies. The aspartic protease has high affinity for peanut oil bodies. The aspartic protease can hydrolyze oil body intrinsic and extrinsic proteins. Abstract: Peanut seeds are rich in oil, which exists as oil bodies (OBs). By extraction, peanut crude OBs are obtained and can be used as a food ingredient. In a previous study, it was found that the crude OBs contained an unknown protease, which hydrolyzed the oleosins. This would disrupt the integrity of OBs, and therefore, affect their physical and oxidative stability. In this study, the protein composition of crude OBs and some properties of the unknown protease were examined. The results showed that the protease was a two-chain (32 and 9 kDa) aspartic protease, which showed high affinity for OBs. The optimal pH and temperature for oleosin hydrolysis by the protease were pH 4.0 and 60 °C. Interestingly, the aspartic protease not only hydrolyzed OB intrinsic proteins (oleosin, caleosin, and steroleosin), but also extrinsic proteins (especially Ara h 1 allergen and 26–30 kDa arachin).